Comparison of direct site endovascular repair utilizing expandable polytetrafluoroethylene stent grafts versus standard vascular shunts in a porcine (Sus scrofa) model. Issue 3 (September 2017) - Davidson, Anders J.; Neff, Lucas P.; Grayson, J. Kevin; Clement, Nathan F.; DeSoucy, Erik S.; Simon Logan, Meryl A.; Abbot, Christopher M.; Sampson, James B.; Williams, Timothy K.
Abstract : INTRODUCTION: The small diameter of temporary vascular shunts for vascular trauma management may restrict flow and result in ischemia or early thrombosis. We have previously reported a clinical experience with direct, open surgical reconstruction using expandable polytetrafluoroethylene stent grafts to create a "sutureless" anastomosis as an alternative to standard temporary vascular shunts. We sought to characterize patency and flow characteristics of these grafts compared with standard shunts in a survival model of porcine vascular injury. METHODS: Twelve Yorkshire-cross swine received a 2-cm-long near-circumferential defect in the bilateral iliac arteries. A 14 Fr Argyle shunt was inserted into one randomly assigned artery, with a self-expanding expandable polytetrafluoroethylene stent deployed in the other. At 72 hours, conduit patency was evaluated by angiography. Arterial flow measurements were obtained at baseline, immediately after intervention, and after 72 hours via direct measurement with perivascular flow meters. Blood pressure proximal and distal to the conduits and arterial samples for histopathology were obtained during the terminal procedure. RESULTS: Angiography revealed no difference in patency at 72 hours ( p = 1.0). While there was no difference in baseline arterial flow between arteries ( p = 0.63), the stent grafts demonstrated significantly improved blood flow compared with shunts both immediately after intervention (390 ± 36 mL/min vs. 265 ± 25 mL/min, p = 0.002) and at 72 hours (261 ± 29 mL/min vs. 170 ± 36 mL/min, p = 0.005). The pressure gradient across the shunts was greater than that of the stent grafts (11.5 mm Hg [interquartile range, 3–19 mm Hg] vs. 3 mm Hg [interquartile range, 3–5 mm Hg], p = 0.013). The speed of deployment was similar between the two devices. CONCLUSIONS: Open "sutureless" direct site repair using commercially available stent grafts to treat vascular injury is a technically feasible strategy for damage control management of peripheral vascular injury and offers increased blood flow when compared with temporary shunts. Furthermore, stent grafts may offer improved durability to extend the window until definitive vascular repair. The combination of these traits may improve outcomes after vascular injury. LEVEL OF EVIDENCE: Epidemiologic/Prognostic, level III. Abstract : Supplemental digital content is available in the text.